The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.46912/jbrcp.167
|View full text |Cite
|
Sign up to set email alerts
|

Profile and Outcome of Medical Emergencies in a Teaching Hospital in the Commercial City of Aba, Southeast Nigeria

Abstract: Medical conditions present at the Accident and Emergency (A&E) or Emergency Department (ED) very often. Outcome of medical emergencies depends, among other factors, on the age of patients, gender, socioeconomic factors, medical conditions, their severity, time of patients' presentations, quality of care/treatment given and the available resources (manpower and facilities) in the A&E. There is a paucity of published literature on medical emergencies outcome in Aba, Southeast Nigeria. This study, therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This was not surprising, as hypertension was the most documented comorbid condition recorded in the study, and stroke and heart failure are long-term complications of hypertension. Many studies have also reported non-trauma emergencies as the leading cause of death in the AEU [16,17,19,20,24] with stroke and other cardiovascular diseases being the most common among the non-trauma causes [2,14,16,18,[20][21][22], [25]. In general, most previous studies agree that the death rate from trauma is higher in males than in females [8,[26][27][28][29].…”
Section: Discussionmentioning
confidence: 94%
“…This was not surprising, as hypertension was the most documented comorbid condition recorded in the study, and stroke and heart failure are long-term complications of hypertension. Many studies have also reported non-trauma emergencies as the leading cause of death in the AEU [16,17,19,20,24] with stroke and other cardiovascular diseases being the most common among the non-trauma causes [2,14,16,18,[20][21][22], [25]. In general, most previous studies agree that the death rate from trauma is higher in males than in females [8,[26][27][28][29].…”
Section: Discussionmentioning
confidence: 94%